Comparing the Effectiveness of Barlow’s Unified Transdiagnostic Treatment and Acceptance and Commitment Therapy on Cognitive Emotion Regulation and Psychological Flexibility in Women Bereaved by COVID-19 - Eslami, Mansoreh; khoshakhlagh, Hassan; Rezaei Dehnavi, Sedigheh; Zare Neyestanak, Mohammad (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to compare the effectiveness of Barlow’s Unified Transdiagnostic Treatment (UTT) and Acceptance and Commitment Therapy (ACT) on cognitive emotion regulation and psychological flexibility in women who lost their spouses due to COVID-19. Method: This study employed a quasi-experimental design with a pretest-posttest and a 2-month follow-up, including a control group. The statistical population consisted of women who experienced spousal bereavement due to COVID-19 and were referred to Imam Khomeini Hospital in Tehran in 2022. Using purposive sampling, 51 participants were selected and randomly assigned to three groups of 17. Due to attrition in the ACT group, one participant was randomly removed from each of the other two groups to equalize group sizes. Consequently, data from 16 participants in each group were analyzed. The first experimental group received Acceptance and Commitment Therapy based on the protocol of Hayes et al. (2004), and the second experimental group received Barlow’s Unified Protocol over nine weekly 90-minute sessions. The research instruments included the Cognitive Emotion Regulation Questionnaire (Garnefski & Kraaij, 2007) and the Cognitive Flexibility Inventory (Dennis & Vander Wal, 2010). Data were analyzed using repeated measures ANOVA. Results: The findings indicated that both interventions significantly improved cognitive emotion regulation and psychological flexibility in women bereaved by COVID-19, and these treatment effects remained stable at follow-up (p < .001). Furthermore, no significant difference was observed between the two interventions in improving emotion regulation; however, ACT was significantly more effective than UTT in enhancing psychological flexibility. Conclusion: Both Acceptance and Commitment Therapy and Barlow’s Unified Transdiagnostic Treatment can be considered effective interventions for improving cognitive emotion regulation and psychological flexibility in women who have lost their spouses to COVID-19.